A Structural Equation Modeling on Factors Related to the Brand Loyalty of Diners to Certified Thai Restaurants in the United States - Auapinyakul, Woravat (Animo Repository, 2019)
The study examines a set of factors for their influence on the brand loyalty of diners to certified Thai Restaurants in the United States. Specifically, the study investigates the hypothesized direct or indirect influences of image, service quality, customer expectations, sensory perception, and customer satisfaction on brand loyalty. A total of 620 diners who had eaten at least once in certified Thai restaurants in the United States were interviewed using a self-accomplished questionnaire. Results confirm almost all of the hypothesized influences of the structural equation model variables on loyalty. Customer satisfaction is the factor having the strongest influence on loyalty, followed by customer expectations, service quality, image, and sensory perception in that order. Overall, the variances in loyalty, customer satisfaction, and sensory perception are well-explained by the variables included in the model, but there are nuances in which to appreciate these key findings. Data are useful for Thailand as it continues to deepen its offshore strategies to further cement the competitiveness of Thai Select and Thai Select Premium restaurants in the United States.